STRONTIUM-90 FUELED THERMOELECTRIC GENERATOR POWER SOURCE--FIVE-WATT U.S. NAVY WEATHER STATION. Final Report - United States. Department of Energy. (Martin-Marietta Corp. Aerospace Div., Baltimore, 1963)
The SNAP-7C 10-watt Sr/sup 90/ thermoelectric generator, the converter, batteries, and weather station housing that were delivered to Antarctica in December 1961 are described. Thermoelectric analysis, thermal analysis, fuel form and shielding requirements, generator assembly, electrical system, operational tests, and environmental testing are discussed. (M.C.G.)